2017
DOI: 10.1021/acs.jpcc.7b05169
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles as a Probe for Amyloid-β Oligomer and Amyloid Formation

Abstract: The process of amyloid-β (Aβ) amyloid formation is pathologically linked to Alzheimer’s disease (AD). The identification of Aβ amyloids and intermediates that are crucial players in the pathology of AD is critical for exploring the underlying mechanism of Aβ aggregation and the diagnosis of the disease. Herein, we performed a gold nanoparticle (AuNP)-based study to detect the formation of Aβ amyloid fibrils and oligomers. Our results demonstrate that the intensity of the surface plasmon resonance (SPR) absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 63 publications
1
37
0
Order By: Relevance
“…They have become a very useful tool in immunoassay and nucleic acid analysis and have been widely applied in food safety, environmental protection and clinical laboratories. [15][16][17] However, methods to detect AuNPs or AuNP-labelled substances are limited to colorimetric, photometric, electron microscopy, and photomicrography with the help of visual methods. This results in difficulties in the accurate determination of AuNPs or AuNP-labelled substances.…”
Section: Introductionmentioning
confidence: 99%
“…They have become a very useful tool in immunoassay and nucleic acid analysis and have been widely applied in food safety, environmental protection and clinical laboratories. [15][16][17] However, methods to detect AuNPs or AuNP-labelled substances are limited to colorimetric, photometric, electron microscopy, and photomicrography with the help of visual methods. This results in difficulties in the accurate determination of AuNPs or AuNP-labelled substances.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that large AuNPs accelerate Aβ fibrillation, whereas small AuNPs significantly suppress the inhibition process. Esmail et al have used AuNPs to detect the formation of Aβ amyloid fibrils and oligomers 24 . They have demonstrated that the surface plasmon resonance (SPR) band intensity of the AuNPs is sensitive to the presence of oligomers of both Aβ40 and an Aβ40 mutant.…”
mentioning
confidence: 99%
“…These are consistent with our previous report that the aggregation of this peptide produces stable oligomers instead of proceeding to form fibrils in phosphate buffer. [8] The Lys16 residue is in close proximity to the hydrophobic core “L 17 VFFA 21 ” region, which is essential for Aβ oligomer and fibril formation. [9] K16Nle mutagenesis dramatically increases the hydrophobicity of the peptide (Table S1).…”
mentioning
confidence: 99%